MRT in Surabaya without Land Acquisition by Utilizing the River Routes and the Existing Single Track Railroad - Gunawan; Daniel, Basil David; Caroline, Jenny (International Journal of Architecture and Urbanism, 2025)
Traffic congestion that occur between the city of Surabaya and the surrounding buffer cities which are 30 to 50 kilometers away are caused by the increasing use of private vehicles and the decreasing use of public transportation because it is considered that the process will be complicated and travel ineffective. This will cause an imbalance between the capacity of the highway and the number of vehicles, resulting in traffic congestion, especially during peak hours. To overcome this problem, improvements are made to sustainable and community liveability in the form of optimal utilization of existing properties in the city, including rivers and existing railroad. With the background above, this paper will present the idea of a solution to overcome traffic congestion by utilizing the drainage channel or rivers and the single tracks railroad to become MRT lanes. This transportation system innovation will be proposed as an evaluation of the Indonesian Railroad Master Plan (2018 to 2030), specifically to be implemented in the city of Surabaya and surrounding.